Solving System of a Linear Fractional Differential Equations by Using Laplace Transformation - Shaker Rashid; Yaseen Mustafa (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper, we provide a solution to the system of non-integer differential equation of order  0 < q < 1, by the technique of Laplace transformation and with interest to property of Mittag-Leffler function, with the help of  the programming technique of Maple.